Reconstruction of the Indian Ocean Tsunami in 2004 in Sabang Based on the Current Land Cover for Tsunami Evacuation Sites Recommendations - Jihad, Abdi; Al Atas, Zaenal; Banyunegoro, Vrieslend Haris; Anugrahningrum, Herdiyanti Resty; Ginting, Rika Adenila; Putra, Kurniallah Perdana; Rusdin, Andi Azhar; Ardiyansyah, Tommy; Yatimantoro, Tatok (Universitas Negeri Surabaya, 2023)
Sabang City has grown in term of city’s population as well as the tourism activity. The development also meant there are more area that has been used when compared to the time before the 2004 tsunami. This research was developed to re-identify tsunami-prone zones with the current land cover condition in Sabang City and to provide recommended safe locations, alternative evacuation routes, and additional evacuation sites. We used Cornell Multi-grid Coupled Tsunami Model (COMCOT) to carried out the tsunami simulation added with updated land cover to provide more accurate simulation model. The simulation pointed out several tsunami hazard zones in Sabang City, such as Balohan, Kuta Ateuh, and Iboih with expected tsunami heights to be more than 3 meters and arrival time less than 60 minutes. Those areas then surveyed to develop recommendations for tsunami risk reductions. The recommendations included nine additional evacuation buildings are proposed, three sites in each zone. Another recommendation is in form of evacuation routes in each zone to complement existing routes stated in RTRW document.